THE EFFECTS OF STUDENTS' LEARNING STYLE PREFERENCES ON THEIR ACADEMIC ACHIEVEMENT IN SCIENCE AND TECHNOLOGY CLASS - Evrim URAL (Fırat University, 2019)
One of the steps to be taken to increase the quality of education is to get to know the students. Studies show that students learn in different ways and that i